Defence is the best offence: invasive prey behaviour is more important than native predator behaviour. (April 2018) - Mennen, Gloria J.; Laskowski, Kate L.
Abstract : Finding universal rules that predict the success of potential invaders is difficult given the breadth of interactions that occur between the invader and the other species in its new range. Among animal species, behavioural traits may play an especially relevant role in mediating these interactions. Whereas the predatory behaviour of invasive predators is especially well documented, less is known about how behaviour may mediate the success of invasive prey species. Here we tested how the behaviour of both an invasive prey species, the amphipod Dikerogammarus villosus, and a common fish predator, the European perch, Perca fluviatilis, affect the outcome of predation events. Invasive D. villosus exhibited significantly greater sheltering and less exploratory behaviour than a naturalized amphipod Gammarus roeseli . This increased sheltering behaviour in the invasive amphipod appears to have a major functional consequence as this species was far less likely than the naturalized amphipod to be predated by the perch. Contrary to our predictions, the behaviour of the individual perch had no influence on consumption of either amphipod species, suggesting that amphipod behaviour was the key determinant of the success of a predation event. Our results highlight the importance of prey behaviour during predation events and emphasize that consideration of antipredator behaviour in potentially invasive prey species may help improve predictions of invasion success. Highlights: Interactions between invader and resident species may determine invasion success. Many invasive predator species exhibit high activity and aggression. But active behaviours could be detrimental to invasive prey species. We show an invasive amphipod exhibits extreme hiding and antipredator behaviour. This improves its predation avoidance and perhaps increases its invasion success.